LANGUAGE PERCEPTION AND LANGUAGE PRODUCTION IN EARLY CHILDHOOD: LANGUAGE ACQUISITION - Vivi Velanitta (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Language acquisition is a term to define the process of getting language ability naturally and subconsciously. In language acquisition, there is an optimal time for the children to acquire language optimally. The time is known as critical period that is believed when the critical time is passed by the children without get contact with the language, it will be (almost) impossible to acquire first language and be the native of second language, latter. In other hand, while children acquire language, they will do mistakes (often) and error (rarely). It is related how the children percept language and the way they produce it. In reference to develop language in human, this paper will explore theoretical frameworks related with the steps of children language acquisition which happened in the early childhood related with the transformational process of language perception into language production.